THE THE TRANSLATION OF CULTURAL MARKERS IN ARLINDO, BY ILUSTRALU:: FROM THE BRAZILIAN TO THE ANGLOPHONE POLYSSYSTEM - Moura Aragão, Sabrina; Marques de Souza, Samantha (Revista de Letras, 2025)
The present paper aims at presenting the translation proposal of three pages of the comic Arlindo, written and illustrated by Luíza de Souza — whose artistic name is Ilustralu —, selected and categorized according to the classification of cultural markers in comics proposed by Aragão (2018), namely: visual, iconic and verbal-iconic. The commented translation aims at outlining the translating process that led to the final translation choices, with the understanding that the translator is an intermediary between two cultures, besides the two languages, and that the relation between cultures that is established through the translating act is always based on a power imbalance between these cultures. For this purpose, I make use of the Polysystem Theory, proposed by Even-Zohar (1990), which addresses the relation between literatures, each being their own polysystem, and also being part of a bigger polysystem. Brazilian literature occupies a peripheral position in relation to US-American literature; furthermore, comics also occupy a peripheral position within the Brazilian literary polysystem. Thus, I argue for the importance of the translation of a Brazilian comic to an anglophone context, taking into consideration the relation that may be established between these two polysystems.